2020
DOI: 10.1097/pcc.0000000000002239
|View full text |Cite
|
Sign up to set email alerts
|

Standardized Protocol Is Associated With a Decrease in Continuous Albuterol Use and Length of Stay in Critical Status Asthmaticus*

Abstract: Objectives: The primary aim of this study was to reduce duration of continuous albuterol and hospital length of stay in critically ill children with severe status asthmaticus. Design: Observational prospective study from September 2012 to May 2016. Setting: Medicine ICU and intermediate care unit. Patients: Children greater than 2 years old with admission diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Utility is measured as suitability (appropriateness for a specific population), age span (appropriateness in populations that vary by age), ease of scoring (analysis of complexity), technical feasibility (ability of various providers to perform the score, i.e. auscultation), floor or ceiling effect (presence of unequal distribution of score results), and interpretability (clinical meaningfulness) 7,19 . Our questionnaire data suggest most providers found the BSS technically easy to use and suitable for pediatric patients with bronchiolitis.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Utility is measured as suitability (appropriateness for a specific population), age span (appropriateness in populations that vary by age), ease of scoring (analysis of complexity), technical feasibility (ability of various providers to perform the score, i.e. auscultation), floor or ceiling effect (presence of unequal distribution of score results), and interpretability (clinical meaningfulness) 7,19 . Our questionnaire data suggest most providers found the BSS technically easy to use and suitable for pediatric patients with bronchiolitis.…”
Section: Discussionmentioning
confidence: 94%
“…Although respiratory scores are applied in many clinical contexts, their performance cannot be determined solely on the perception of objectivity or functionality (face value), but rather by their capacity to be discriminative, predictive and evaluative in standardizing care, enhancing decision making, and offering risk stratification 7 . For instance, clinical scores in pediatric asthma are associated with reductions in LOS and continuous albuterol duration 17–19 . To standardize assessment of clinical scores, the COSMIN taxonomy have been proposed and consist of four primary test domains: validity, reliability, responsiveness, and interpretability 13 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A subsequent iteration of that pathway resulted in a significant decrease in LOS and time to albuterol administered every 4 hours (q4h), which is a proxy of clinical recovery and discharge readiness. 20 This growing body of evidence for the management of critical asthma has come out of freestanding children' s hospitals. However, a 2010 survey of .28 000 patients with severe asthma exacerbations revealed that the majority of these patients are admitted to community hospitals without a PICU.…”
mentioning
confidence: 99%